A Rare Case of Primary Intrapulmonary Neurilemmoma Diagnosed in a 43-Year-Old Asymptomatic Man with a Well-defined Intrapulmonary Mass - Serafeim Chrysikos; Maria Kaponi; Christina Triantafillidou; Theodoros Karampitsakos; Argyrios Tzouvelekis; Maria Anyfanti; Konstantinos Marossis; Marios Konstantinou; Rodoula Tringidou; Demosthenes Bouros; Katerina Dimakou (Frontiers in Oncology, 2018)
Neurilemmoma (NL), also termed schwannoma, presents as a well-circumscribed and encapsulated mass in the human body and is almost always solitary. CT scan of a patient with NL shows a round, ovoid, or lobulated well-demarcated solid mass of soft tissue density. Primary intrathoracic neurogenic tumors location varies. However, the development of such tumors is by far more common in the costovertebral angle of the posterior mediastinum. Here, we report a rare case of a 43-year-old patient, never smoker and previously healthy, who presented with a mass adjacent to the right pulmonary hilum. This was an incidental finding on a chest X-ray after annual checkup at his workplace. The diagnosis was primary intrapulmonary NL. Primary intrapulmonary NL is an extremely rare tumor. However, based on the above, chest CT findings of a well-defined solid mass in an asymptomatic patient should raise the suspicion of NL, irrespective of the tumor localization.